Teacher Round Table - SHELLY UNSICKER-DURHAM; SHAISTA FENWICK; NAJAH AMATULLAH HYLTON; SUZANNE SUTTON; CONNOR WOODARD (University of Oklahoma Libraries, 2022)
Study and Scrutiny has focused on the publication of critical and empirical studies surrounding the scholarship and critical merits of Young Adult literature. Because other journals provide a space for pedagogical practices concerning YA, the editors have intentionally shied away from explaining to teachers how to teach a particular title in a particular way. Still, the intention of the journal has been, in part, to support the learning of secondary students as readers and the classroom practices of their teachers. This section hopes to serve as a space to open the conversation surrounding YA literature, its critical merits, and ways that the research might serve teachers as they make curriculum choices about both texts and strategies. The idea is to bring teachers, as intellectuals, into conversation surrounding the scholarship of a featured study. For this issue, four Oklahoma teachers from four different school districts focus on Arianna Banack's article "Connecting and Critiquing the Canon: Pairing Pride and Pride and Prejudice."